EFEKTIVITAS SISTEM APLIKASI FINEST PADA FINANCE CENTER TERHADAP PROSES VERIFIKASI TRANSAKSI PEMBAYARAN DI PT TELKOM INDONESIA - Azizah, Nur; Rahmah, Firda (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2024)
In the era of digitalization, technology advances business with application systems that increase efficiency. A slow verification process can delay payments, and affect liquidity and the company's financial balance. Therefore, many companies use application systems to support financial management and speed up payment transaction verification. This research uses quantitative methods with a survey and observation approach to examine the relationship between variables. Primary data is obtained directly from surveys and observations. Data collection was carried out through observation, questionnaires, and literature study. Literature studies involve collecting and analyzing relevant library data, articles, and online sources. Periodic evaluation, development, and training are carried out to ensure the relevance and understanding of system features in the long term. The payment transaction verification process at PT Telkom Indonesia is carried out systematically and effectively using the Finest application. This application makes verification easier, increases productivity, and provides control features